Integrating Animated Video to Cause Effect Essay Writing Learning Material - Aula, Farisa Afza; Hoesny, Mariana Ulfah; Budianto, Aris (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing is a fundamental skill that supports students’ critical thinking, yet many still struggle due to ineffective teaching methods. This study was aimed at developing cause-effect writing learning material integrated with animated video. Using the Design and Development Research (DDR) approach by Richey and Klein (2007) and applying the ADDIE model, data were collected through questionnaires and interviews during the analysis stage. The result of this study is one chapter of writing learning material specific for cause-effect essay. There are reading texts, definitions of the essays, the structure of the essays, writing tips, a grammar corner, and graded exercises. While the video explained aspects of cause-effect essay, and the grammar required to write the essay.